2006
DOI: 10.1007/s00441-005-0148-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis of hepatoma spheroid formation: roles of E-cadherin and β1-integrin

Abstract: A spheroid is an in vitro multicellular aggregate that provides a microenvironment resembling that of normal tissue in vivo. Although cell adhesion molecules such as integrins and cadherins have been implicated in participating in the process of spheroid formation, little is known about the timing of their action. In this study, we have employed an image-based quantitative method to investigate the compactness of cell aggregates during hepatoma spheroid formation in a dynamic fashion. By modulating beta1-integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
201
2
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(230 citation statements)
references
References 44 publications
(54 reference statements)
18
201
2
9
Order By: Relevance
“…In contrast, downregulation of E-cadherin function causes reduced viability, suggesting that proliferation signals downstream of E-cadherin activation contribute to ovarian cancer cell survival. Similar results have been observed in squamous cell carcinoma [89], hepatoma [90] and Ewing tumor cells [91].…”
Section: Functional Impact Of Phenotypic Plasticity: Why Gain E-cadhesupporting
confidence: 88%
“…In contrast, downregulation of E-cadherin function causes reduced viability, suggesting that proliferation signals downstream of E-cadherin activation contribute to ovarian cancer cell survival. Similar results have been observed in squamous cell carcinoma [89], hepatoma [90] and Ewing tumor cells [91].…”
Section: Functional Impact Of Phenotypic Plasticity: Why Gain E-cadhesupporting
confidence: 88%
“…This was in contrast with the activation of EMT pathway [45] but in consistent with the expression of liver cancer tissue used in this study. Previously study also shows E-cadherin regulates the establishment of the adherens junctions and the expression of E-cadherin is upregulated when forming compact tumor spheroids [46]. The upregulation of E-cadherin expression in HCC cells cultured within ALG beads might be caused by compact spheroids formation (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Long-term live cell imaging showed that the expression of N-cadherin led to an increase in the rate of cell aggregation compared with untransfected involves integrin -ECM interactions and only in the later stages-after 20 h-are cadherin interactions considered to contribute to the process [23]. However, these results could be cell-type specific.…”
Section: Intercellular Binding-dependent Spheroid Formationmentioning
confidence: 99%